1974
DOI: 10.2307/3113198
|View full text |Cite
|
Sign up to set email alerts
|

The Truman Administration and the Enlistment of the Aviation Industry in Postwar Defense

Abstract: At the end of World War II, by far the most significant pressure for integrating the aviation industry into national defense planning came neither from the major aircraft firms nor from the military. Instead, the Truman administration played the leading role in forging an important link in what later came to be called the “military-industrial complex.” Smaller businessmen and local politicians proved constant and eager supporters of that policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…269 The War Production Board reported that "at the beginning of our war program 175,000 companies were providing 70% of the nation's manufacturing output and 100 corporations were producing 30% Today, two and one-half years later, this ratio has been reversed; now 100 corporations hold 70% of the war and essential civilian contracts, while 175,000 small companies hold 30%" ( Notes "Procurement Profits" are the unweighted averages of the ten companies listed in Table 5.4. 288 The history of the production and profits of the shipbuilding and aircraft industries thus seems inconsistent with the notion of a military-industrial complex: defense-related industries fared poorly in comparison to other businesses during the war and fared still worse in relation to other businesses between 1945 and 1950 (refer to Table 5.4). After-tax profit margins are "Income taxes" subtracted from "Total receipts less total deductions" and then divided by "Total receipts."…”
Section: The Military-industrial Complexmentioning
confidence: 99%
“…269 The War Production Board reported that "at the beginning of our war program 175,000 companies were providing 70% of the nation's manufacturing output and 100 corporations were producing 30% Today, two and one-half years later, this ratio has been reversed; now 100 corporations hold 70% of the war and essential civilian contracts, while 175,000 small companies hold 30%" ( Notes "Procurement Profits" are the unweighted averages of the ten companies listed in Table 5.4. 288 The history of the production and profits of the shipbuilding and aircraft industries thus seems inconsistent with the notion of a military-industrial complex: defense-related industries fared poorly in comparison to other businesses during the war and fared still worse in relation to other businesses between 1945 and 1950 (refer to Table 5.4). After-tax profit margins are "Income taxes" subtracted from "Total receipts less total deductions" and then divided by "Total receipts."…”
Section: The Military-industrial Complexmentioning
confidence: 99%
“…If a government chooses to source armaments from private companies it may also reap the benefits of the innovation and development work performed there. However, such a strategy may also lead to the capture of the military establishment by companies and the creation of military industrial complexes (Bernstein & Wilson, 2011;Cooling, 1981;Cuff, 1978;Gholz, 2011;Koistinen, 1967;Mrozek, 1974;Wills, 2011).…”
mentioning
confidence: 99%